The Effect of Job Satisfaction and Work Discipline on Employee Performance at Perumda Air Minum Lamongan - Devita Ayu Kristanti (RTTM, 2024)
Human resource management is the science and art of managing employee relationships and roles so that they contribute effectively and efficiently to the success of businesses, employees and social organizations (Hasibuan, 2019: 10). Lamongan Regional Drinking Water Company, employee performance is considered to be an important factor. Therefore, performance is the ability of a person or group of people to carry out work in accordance with their responsibilities in order to achieve the expected results. The population of this study was employees of the Lamongan Regional Drinking Water Company, totaling 150 people and calculated using the Slovin formula, the sample result was 60 people. The analytical model used in this research is multiple linear regression. Based on the results of the regression test, the Y value is 11.198 + 0.447X1 + 1.324X2. From this value it can be concluded that work discipline has the highest influence on employee performance because it has the highest beta value, namely 1.324.